PENGARUH PENGAWASAN KERJA, KOMITMEN KARYAWAN DAN KOMUNIKASI TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BPR PIJER PODI KEKELENGAN SIMPANG POS MEDAN - Lumbanbatu, Jhon David; Sinaga, Ria Veronica; Sembiring, Sabeth (UNIKA Santo Thomas, 2021)
This study aims to examine and analyze the effect of Work Supervision, Employee Commitment and Communication on Employee Performance at PT. BPR Pijer Podi Kekelengan Medan Post Intersection. The sampling technique used is saturated sampling method and the analysis method used is multiple linear regression. From the research results, the multiple regression equation is as follows: PKK = 1.059+ 0.287PK + 0.309KK + 0.135K + ei. This means that the Employee Commitment (KK) variable has a greater influence on employee work performance, because the regression coefficient is greater, namely 0.309. The results of the t test show that the employee commitment variable has a positive and significant effect on employee work performance where the t value (4.233)> the t table value (1.682) and the significant value 0.000